The Effect of Concept Map Learning, Problem Solving and Achievement Motivation on Indonesian Learning Outcomes - Dwi Setyo Larasati Deddy Kurniawati; Achmad Noor Fatirul; Atiqoh (Jurnal Mantik, 2022)
The purpose of this development is this development is to produce an M-Learning learning media in the form of a digital book as an interesting source of information with Indonesian language subject matter. The development model used in the development of interactive learning multimedia is the Borg & Gall model. The stages of development research on the Borg & Gall model consist of ten steps, namely: (a) research and data collection, (b) planning, (c) initial product development, (d) initial product trial/limited trial, (e ) improvement of the initial product, (f) wider field trial, (g) improvement of the product resulting from wider field test, (h) final product trial, (i) revision or refinement of the final product, (j) dissemination and implementation. The results of this development research are that this Mobile Learning Media Product has a material feasibility level, learning design feasibility, and learning media feasibility. While the level of small group trials and field trials with qualifications is very feasible and does not need to be revised.